CDK9 as a Valuable Target in Cancer: From Natural Compounds Inhibitors to Current Treatment in Pediatric Soft Tissue Sarcomas - Cassandri, Matteo; Fioravanti, Rossella; Pomella, Silvia; Valente, Sergio; Rotili, Dante; Del Baldo, Giada; De Angelis, Biagio; Rota, Rossella; Mai, Antonello (Frontiers in Pharmacology, 2020)
Cyclin-Dependent Kinases (CDKs) are well-known reliable targets for cancer treatment being often deregulated. Among them, since the transcription-associated CDK9 represents the sentry of cell transcriptional homeostasis, it can be a valuable target for managing cancers in which the transcriptional machinery is dysregulated by tumor-driver oncogenes. Here we give an overview of some natural compounds identified as CDK inhibitors with reported activity also against CDK9, that were taken as a model for the development of highly active synthetic anti-CDK9 agents. After, we summarize the data on CDK9 inhibition in a group of rare pediatric solid tumors such as rhabdomyosarcoma, Ewing’s sarcoma, synovial sarcoma and malignant rhabdoid tumors (soft tissue sarcomas), highlighting the more recent results in this field. Finally, we discuss the perspective and challenge of CDK9 modulation in cancer.